Pengaruh Konten Instagram @Baweantourism terhadap Tingkat Wawasan Followers - Nuzulur Rahman; Agus Ainul Yaqin M.S (JURNAL PARADIGMA MADANI : Ilmu Sosial, Politik dan Agama, 2025)
The rise of social media has transformed how people access information, including tourism insights. This study analyzes the influence of Instagram content on @baweantourism toward followers' knowledge levels. Using a descriptive quantitative approach, data were collected through questionnaires and analyzed statistically. The study is grounded in mass communication and media effects theory. Findings reveal a positive and significant impact of Instagram content on user awareness, indicated by t-count (19.070) > t-table (1.982) and a significance level of 0.000 < 0.05. The study concludes that social media serves as an effective tool for promotion and education in raising public knowledge about local destinations such as Bawean.